Compensation, Perceptions of Organizational Culture, and Turnover Intention: Does Organizational Commitment Mediate the Relationship? - Aditya Candra Laksmana; Heru Kristanto (Journal of Economics, Business, and Accountancy Ventura, 2023)
An employee’s turnover intention to the company is related to organizational commitment, where several factors, such as compensation and perception of organizational culture, strongly support the success of organizational commitment. This research was conducted at PT Andalan Busana Boyolali Indonesia, with 155 respondents who met the requirements with a sampling technique admired as simple random sampling. The data analysis techniques used are Structural Equation Modeling (SEM) through AMOS 21 software and the Sobel test to explore the proposed relationship. The results of this study indicate that compensation and perceptions of organizational culture are directly related to having a positive and significant effect on organizational commitment. Meanwhile, compensation and the perception of organizational culture are directly related to negatively and significantly affecting turnover intentions. In addition, the results also show that employee organizational commitment mediates the effect of compensation and organizational culture perceptions on turnover intentions. This research provides information for companies and related parties to reduce employee turnover rates by increasing financial and non-financial appreciation and evaluating the prevailing organizational culture to provide employee comfort.